DESIGN RESEARCH: KONSEP NILAI TEMPAT PADA OPERASI PENJUMLAHAN BILANGAN DESIMAL DI KELAS V SEKOLAH DASAR - Afriyansyah, Ekasatya Aldila; Putri, Ratu Ilma Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2014)
Many recent studies found that students tended to have difficulty in grasping the concept of the operation of decimal numbers, especially on addition. In order to overcome all the difficulties, this study presents a sequence of classroom activities constructing the understanding of decimals addition. Realistic Mathematics Education (RME) underlies the design of the context and the activities. Design research was chosen as an appropriate means to achieve the aim. It will be conducted in three phases, preliminary design, teaching experiment (first and second cycle), and retrospective analysis. This study involves 6 students (first cycle) and 34 students (second cycle); 4 students. The result of this study can show that a sequence of activities can bring students’ learning from the contextual situation to more formal situation. Students did not think about integer number system when doing decimal number problem. They could do every contextual problem with their reasoning. Learning trajectory on this study can be used for school learning. DOI: https://doi.org/10.22342/jpm.8.1.1857.13-24